Analisis Kepuasan Pengguna Aplikasi Abdi Praja Mobile Menggunakan PIECES dan EUCS - Loujien, Agil Aurora; Saskara, Gede Arna Jude; Darmawiguna, I Gede Mahendra (TIN: Terapan Informatika Nusantara, 2025)
The Abdi Praja Mobile application is a system owned by KPN Abdi Praja to support the digital transformation of the cooperative, particularly in providing easier access to financial information for its members. Through this application, members are expected to receive services that are faster, more accurate, and more efficient without needing to visit the cooperative office directly. However, in its implementation, there are still several obstacles that affect the level of user satisfaction, such as limited features, a registration process that is not yet simple, and technical issues that occur at certain times. These conditions indicate the need for a comprehensive evaluation so that the application’s development can be more targeted and aligned with the needs of its members. This study aims to evaluate user satisfaction, analyze the influence of each variable contained in the PIECES and EUCS methods, and formulate improvement recommendations based on the results of the analysis. The findings show that the variables Performance, Information, Economic, Control, Efficiency, Service, and Content have a positive and significant impact on user satisfaction. This indicates that these aspects are perceived as beneficial by members and contribute to their experience in using the application. On the other hand, the variables Accuracy, Format, Ease of Use, and Timeliness do not have a significant influence, suggesting that these elements require more attention in future application development. The recommendations proposed include optimizing system reliability and stability, providing automatic notifications for financial information, developing more comprehensive service features, simplifying the registration process, strengthening data security, improving application accessibility across devices, and providing a 24-hour support service or call center to ensure that members can receive assistance whenever needed.